B-Type Natriuretic Peptides Help in Cardioembolic Stroke Diagnosis: Pooled Data Meta-Analysis. Issue 5 (May 2015) - Llombart, Víctor; Antolin-Fontes, Albert; Bustamante, Alejandro; Giralt, Dolors; Rost, Natalia S.; Furie, Karen; Shibazaki, Kensaku; Biteker, Murat; Castillo, José; Rodríguez-Yáñez, Manuel; Fonseca, Ana Catarina; Watanabe, Tetsu; et al.
Abstract : Background and Purpose—: Determining the underlying cause of stroke is important to optimize secondary prevention treatment. Increased blood levels of natriuretic peptides (B-type natriuretic peptide/N-terminal pro-BNP [BNP/NT-proBNP]) have been repeatedly associated with cardioembolic stroke. Here, we evaluate their clinical value as pathogenic biomarkers for stroke through a literature systematic review and individual participants' data meta-analysis. Methods—: We searched publications in PubMed database until November 2013 that compared BNP and NT-proBNP circulating levels among stroke causes. Standardized individual participants' data were collected to estimate predictive values of BNP/NT-proBNP for cardioembolic stroke. Dichotomized BNP/NT-proBNP levels were included in logistic regression models together with clinical variables to assess the sensitivity and specificity to identify cardioembolic strokes and the additional value of biomarkers using area under the curve and integrated discrimination improvement index. Results—: From 23 selected articles, we collected information of 2834 patients with a defined cause. BNP/NT-proBNP levels were significantly elevated in cardioembolic stroke until 72 hours from symptoms onset. Predictive models showed a sensitivity >90% and specificity >80% when BNP/NT-proBNP were added considering the lowest and the highest quartile, respectively. Both peptides also increased significantly the area under the curve and integrated discrimination improvement index compared with clinical models. Sensitivity, specificity, and precision of the models were validated in 197 patients with initially undetermined stroke with final pathogenic diagnosis after ancillary follow-up. Conclusions—: Natriuretic peptides are strongly increased in cardioembolic strokes. Future multicentre prospective studies comparing BNP and NT-proBNP might aid in finding the optimal biomarker, the best time point, and the optimal cutoff points for cardioembolic stroke identification. Abstract : Supplemental Digital Content is available in the text.